Movement-Related Activity of Human Subthalamic Neurons during a Reach-to-Grasp Task - Pötter-Nerger, Monika; Reese, Rene; Steigerwald, Frank; Heiden, Jan Arne; Herzog, Jan; Moll, Christian K. E.; Hamel, Wolfgang; Ramirez-Pasos, Uri; Falk, Daniela; Mehdorn, Maximilian; Gerloff, Christian; Deuschl, Günther; et al. (Frontiers in Human Neuroscience, 2017)
The aim of the study was to record movement-related single unit activity in the human subthalamic nucleus (STN) during a standardized motor task of the upper limb. We performed microrecordings from the motor region of the human STN and registered kinematic data in twelve patients with Parkinson’s disease undergoing deep brain stimulation surgery (seven women, mean age 62.0 ± 4.7 years) while they intraoperatively performed visually cued reach-to-grasp movements using a grip device. Single unit activity was analyzed offline in relation to different aspects of the movement (attention, start of the movement, movement velocity, button press) in terms of firing frequency, firing pattern, and oscillation. During the reach-to-grasp movement, 75/114 isolated subthalamic neurons exhibited movement-related activity changes. The largest proportion of single units showed modulation of firing frequency during several phases of the reach and grasp (polymodal neurons, 45/114), particularly an increase of firing rate during the reaching phase of the movement, which often correlated with movement velocity. The firing pattern (bursting, irregular, or tonic) remained unchanged during movement compared to rest. Oscillatory single unit firing activity (predominantly in the theta and beta frequency) decreased with movement onset, irrespective of oscillation frequency. This study shows for the first time specific, task-related, single unit activity changes during the reach-to-grasp movement in humans.